Electronic concept maps strategy and its Effect on the Level of Cognitive Achievement of some Artistic skills in volleyball - Sadoon, Aws; Saleh, Mohammed (Journal of Physical Education, 2020)
The study aimed at adjusting a test for the cognitive achievement for some artistic skills in volleyball for sophomores at the College of Physical Education and Sports Science as well as identifying the effect of using Electronic concept maps strategy educational units on the level of cognitive achievement of some artist skills in volleyball for the subjects of the study. The researchers adopted the experimental method and study subjects were (15) students for each experimental and control group. The main inquiry-based experiment was executed with one educational session per week for period of (8) weeks. The results of the study indicated a significant effect on the results of the cognitive achievement test between the two groups in favor of the Electronic concept maps strategy applied on experimental group.